THE IMPACT OF NURSING STAFF IN HEALTH MANAGEMENT PROGRAMS - Fatma Ali Alhaqab, Mohammed Hamoad Mohammed Al-Hebbi, Salman Mesfer Almutairi, Hamoud Abdullah Alshahrani, Eiman Mohsen Zober, Riadah Howidi Aldosari, Hussain Owyed Alanazi, Hammad Meshari Alharthi, ,; Fahda Muhaisen Alshaibani, Nawal Mohammed Ali Al Harithi, Khlood Abdalaziz Alhoti, Sarah Alawi Alshubbar, Seham Sulaiman Al Saeed, Fatimah Ibrahma Al Salih, Wazan Mueidh Al Onazi, (Chelonian Research Foundation, 2022)
The purpose of this research is to determine the relationship between nurse staffing techniques and nurse and patient outcomes by methodically reviewing and synthesizing the available data. For papers published in English, a search of Web of Science, CINAHL (EBSCO), and MEDLINE (EBSCO) was done. The introduction of a required minimum nurse-to-patient ratio was shown to increase nurse outcomes in every study that examined nurse outcomes; however, results on patient outcomes were not entirely conclusive. There is still a dearth of data about how certain nurse staffing strategies affect patient and nurse outcomes. Future research on the effects of different staffing approaches on results is needed to inform this core area of practice and management. Keywords: Patient outcomes, nurse staffing, systematic review, workload approaches, nurse outcomes